Characterization of an Antioxidant and Antimicrobial Extract from Cool Climate, White Grape Marc - Kenneth J. Olejar; Arianna Ricci; Simon Swift; Zoran Zujovic; Keith C. Gordon; Bruno Fedrizzi; Andrea Versari; Paul A. Kilmartin (MDPI AG, 2019)
Valorization of agricultural waste has become increasingly important. Wastes generated by wineries are high in phenolic compounds with antioxidant and antibacterial properties, which contribute to phytotoxicity, making their immediate use for agricultural means limited. Utilizing a water-based extraction method, the phenolic compounds from winery waste were extracted and purified. The resulting extract was characterized for phenolic composition using high-pressure liquid chromatography-ultraviolet/visible and electrochemical detectors (HPLC-UV/Vis, ECD) for monomers, and spectral assessment of the tannins present using attenuated total reflectance- Fourier transform infrared (ATR-FTIR), FT-Raman, and solid-state nuclear magnetic resonance (SSNMR) spectroscopies. The extract’s antioxidant activity was assessed by the scavenging of the 2,2-diphenyl-1−picrylhydrazyl (DPPH) radical and Folin-Ciocalteu total phenolic assay, and was found to be as effective as a commercially obtained grape extract. The extract’s antimicrobial efficacy was tested for minimum bactericidal concentration using Candida albicans, Escherichia coli 25922, and Staphylococcus aureus 6538, which resulted in greater efficacy against gram-positive bacteria as shown over gram-negative bacteria, which can be linked to both monomeric and tannin polyphenols, which have multiple modes of bactericidal action.